Pengembangan Sistem Arsip Dinamis Kontrak Tower Menggunakan Metode DevOps Berbasis Web - Arbin Rante (TIN: Terapan Informatika Nusantara, 2026)
The management of tower lease renewal warning letters at PT Indosat Ooredoo Hutchison (IOH) faces various challenges, including process inefficiency, recording errors, and limited data visibility due to reliance on manual processes that have not been systematically structured. These conditions have led to slow administrative responses and an increased risk of delays in handling alternative tower replacement mitigation. This study aims to design and develop a web-based dynamic archive information system using the DevOps method to improve software development effectiveness while optimizing operational services within the Tower Lease Provider (TLP) department at PT IOH. DevOps was selected for its ability to continuously integrate development and operations processes, thereby accelerating software release cycles and improving system quality on an ongoing basis. The research was conducted at PT IOH's Jakarta office during the period of April–June 2026, involving four tower providers as informants and one internal TLP representative. Research stages included requirements analysis, database design using Entity Relationship Diagrams (ERD) and Physical Data Models (PDM), implementation of monitoring features, automated notifications, and reporting, through to deployment via the TLP SYSTEM ARSIP application. Testing was carried out using the Black Box Testing method, confirming that all core functions performed as expected. The results demonstrate that the system operates stably, with improved recording accuracy, a reduction in administrative processing time of up to 60–70%, and a decrease in recording errors of up to 80% compared to the previous manual process. Through DevOps implementation, PT IOH has acquired a reliable and adaptive digital platform responsive to evolving operational needs in tower lease renewal management.